The Effect of Attractiveness, Accessibility, and Facilities on the Decision to Visit the Belagaone Mangrove Tourist Object : JEL Classification: L83, M31, R11, R58, Z32 - Darmiah Darmiah; M. Nasir Hamzah; Nurmadhani Fitri Suyuhti (Journal La Bisecoman, 2026)
This study examines the effect of attractiveness, accessibility, and facilities on tourists’ decision to visit the Belagaone Mangrove tourist object in Nunukan Regency. The study was motivated by the unstable and declining number of tourist visits from 2020 to 2024, indicating the need to evaluate the factors that shape visitor interest and decision making. A quantitative explanatory approach was employed using survey data collected from 100 respondents who had visited the destination. The research variables consisted of attractiveness, accessibility, and facilities as independent variables, while the decision to visit served as the dependent variable. Data were analyzed using classical assumption tests and multiple linear regression. The normality test showed that the data were normally distributed, while the multicollinearity test confirmed that the independent variables were free from multicollinearity. The regression results revealed that attractiveness, accessibility, and facilities each had a positive and significant effect on the decision to visit. The simultaneous test also showed that the three variables collectively influenced tourists’ visiting decisions. The coefficient of determination indicated that these variables explained 37.6 percent of the variation in visiting decisions, while the remaining 62.4 percent was influenced by other factors outside the model, such as promotion, ticket prices, destination image, and tourism trends. These findings suggest that improving the ecological appeal, access quality, and supporting facilities of Belagaone Mangrove is essential to strengthen visitor interest and support sustainable tourism development in Nunukan Regency.